2018
DOI: 10.3390/ijms19102998
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Physical Stimuli on Calcium Channels in Chondrogenic Differentiation of Mesenchymal Stem Cells

Abstract: Human mesenchymal stem cells (hMSC) are becoming increasingly popular in tissue engineering. They are the most frequently used stem cell source for clinical applications due to their high potential to differentiate into several lineages. Cartilage is known for its low capacity for self-maintenance and currently there are no efficient methods to improve cartilage repair. Chondrogenic differentiation of hMSC isolated from different tissues is widely employed due to a high clinical demand for the improvement of c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
58
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1
1

Relationship

2
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 62 publications
0
58
0
Order By: Relevance
“…During this process, progenitor cells differentiate into chondrocytes which later undergo maturation and mineralization, finally resulting in new bone tissue (reviewed in [95]). Whereas the positive effects of EStim on endochondral ossification have been shown in previous studies [29,96,97], there few studies focused on analyzing the effects EStim has on endochondral ossification and MSC chondrogenic differentiation (reviewed in [98]). In our own in vitro studies, we were not able to detect a positive effect of direct current EStim on rat MSC chondrogenic differentiation (unpublished data).…”
Section: Chondrogenesismentioning
confidence: 99%
“…During this process, progenitor cells differentiate into chondrocytes which later undergo maturation and mineralization, finally resulting in new bone tissue (reviewed in [95]). Whereas the positive effects of EStim on endochondral ossification have been shown in previous studies [29,96,97], there few studies focused on analyzing the effects EStim has on endochondral ossification and MSC chondrogenic differentiation (reviewed in [98]). In our own in vitro studies, we were not able to detect a positive effect of direct current EStim on rat MSC chondrogenic differentiation (unpublished data).…”
Section: Chondrogenesismentioning
confidence: 99%
“…Growth factors such as TGF-β, IGF, and bone morphogenetic proteins (BMP)-2,-4,-7 are necessary to stimulate chondrogenic processes and require the presence of calcium ions (Ca 2+ ) to regulate cell functions, such as the synthesis of extracellular matrix components. Physical stimuli have been associated with the regulation of Ca 2+ entry, primarily through voltage-operated calcium channels (VOCCs), transient receptor potential (TRP) channels, and purinergic receptors [22]. Furthermore, VOCC inhibitors have shown to reduce cartilage degradation and the progression of osteoarthritis [23], suggesting their importance in both physiological and pathological milieux.…”
Section: Influencing the Mechanical Environmentmentioning
confidence: 99%
“…To date, ion concentration in the spheroids has not been explored. It has been reported that the mechanical stress affected the activation of calcium ion channels on the cell membrane of MSCs, and the calcium ion-involved signaling played important roles in the differentiation of MSCs [68,69]. On the other hand, the cytoskeleton would be dramatically rearranged during the spheroid formation on CS substrates.…”
Section: Physical and Chemical Factors Affecting Cell Behaviors In Scmentioning
confidence: 99%